The Adaptation of Acceptance of Couple Violence Scale into Turkish: Validity and Reliability Studies - Özcan SEZER (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
This study investigates the validity and reliability of the Turkish adaptation ofAcceptance of Couple Violence Scale (ACVS). The data of research has been attainedfrom 474 (M =243, F=231) high school students who were attending 1st, 2nd and 3thclass and coming from middle socio-economic levels in Malatya. Acceptance of CoupleViolence Scale has 11 items, Likert type and 4 point response format. The constructvalidity of ACVS was conducted by using exploratory factor analysis and varimaxrotation. Single independent factor with the eigenvalue over 1.00 has been found. Thisfactor explained 44% of total variance. To test concurrent validity, correlations betweenscores on ACVS and Aggressiveness Questionnaire were calculated. There was asignificant relationship between scores on the two scales (r= .61). Cronbach alphacoefficient of the scale was found “.87”; test-retest correlation coefficient was “r=.80”.Item-total correlation co-efficiencies vary between “.52” and “.71”. Findings show thatACVS can be used with acceptable level of validity and reliability for high schoolstudents.